2017
DOI: 10.5539/jfr.v7n1p1
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of Major Cassava Varieties in Uganda, Targeted for Industrialisation

Abstract: Uganda is one of the major cassava producing countries in the world. Currently, utilization of cassava is limited to semi-processed products through the informal sector. Cassava has technological potential as a raw material for agro-industrial products, such as flours for baked products, animal feeds and starch. The aim of this study was to investigate the chemical composition of five major cassava varieties grown in Nebbi distict (Uganda), to assess their potential as industrial raw materials. Analysis of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 13 publications
3
14
2
1
Order By: Relevance
“…Various studies on white and yellow cassava, especially on the chemical compositions, have been done. Manano, Ogwok, & Byarugaba-Bazirake (2018) investigated five varieties in Uganda (three sweet, improved, high yields, mosaic-resistant, and two bitter types). The chemical components analyzed include the proximate, mineral, and antinutritional contents.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies on white and yellow cassava, especially on the chemical compositions, have been done. Manano, Ogwok, & Byarugaba-Bazirake (2018) investigated five varieties in Uganda (three sweet, improved, high yields, mosaic-resistant, and two bitter types). The chemical components analyzed include the proximate, mineral, and antinutritional contents.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the 'sweet' or edible varieties have a low cyanide content, hence, they are mainly used for food and food products (Hasmadi et al, 2020). Similarly, Manano et al (2018) reported a significant varietal influence on the levels of starch, calcium, magnesium, cyanonenic glucosides and phytates present in cassava roots. The increasing demand for cassava starch in Nigeria is attracting many medium and large scale industries into the cassava processing sector.…”
Section: Introductionmentioning
confidence: 92%
“…The results reported by Xhibiri (2016) and corroborate well with the findings of this study, and could mean that the fibre in cassava flour is the major cause of the decrease in C5. Manano et al (2018)…”
Section: Mixolab Properties Of Wheat-cassava Composite Flourmentioning
confidence: 99%
“…While gluten is sufficiently extensible to allow the dough to rise, it must be strong enough to prevent gas escaping too readily, which may lead to collapse of the loaf (Kent and Evers, 1994). Cassava flour contains about 1.1 % crude fibre (Manano et al, 2018) compared to approximately 0.5 % crude fibre in wheat (Khan et al, 2019). The elevated fibre content in the wheat-cassava composite flour due to incorporation of cassava flour may puncture expanding gas cells during fermentation leading to reduced loaf volumes (Oladunmoye et al, 2010;.…”
Section: Bread Volume and Bread Densitymentioning
confidence: 99%